Prevalence and predictors of psychological distress in women diagnosed with breast cancer and women without breast cancer: a prospective study of psychological risk and resilience factors. Issue 4 (28th October 2022) - Van Noyen, Lotte; Markovitz, Sabine; Broers, Nick J.; Peters, Madelon L.
Abstract : Supplemental Digital Content is Available in the Text. Abstract: Background: There is some controversy whether psychological distress after breast cancer diagnosis and treatment remains elevated at the long-term follow-up. This study compares the prevalence of psychological distress and anxiety and depressive disorders between patients with breast cancer and women without cancer in a prospective longitudinal design. Moreover, risk and protective factors for psychological distress and anxiety and depressive disorders were compared between the 2 groups. Methods: Two hundred fifty-three patients with breast cancer who underwent surgery completed a series of self-report questionnaires immediately after surgery and 18 months later. In addition, 211 female participants without being diagnosed with cancer were assessed at the same time points. Outcomes are psychological distress as measured with the Hospital Anxiety and Depression Scale and possible presence of anxiety and depressive disorders measured with the Patient Health Questionnaire. Trait resilience, optimism, and neuroticism were investigated as protective or risk factors for the development of psychological distress, anxiety, and depression. Results: We found that the levels of psychological distress and the prevalence of anxiety and depressive disorders are higher in the breast cancer group both at baseline and at 18 months of follow-up. Trait resilience and optimism were observed to be protective factors, and neuroticism was found to be a risk factor in both the breast cancer group and the comparison group. Conclusions: Psychological distress, depression, and anxiety remain elevated in patients with breast cancer over a period of one-and-a-half year. The identified protective and risk factors for these conditions are not unique for patients with breast cancer.